Plant diseases in landrace varieties and hybrid maize cultivated using different technology levels - Alisson Vinicius de Araujo; Delacyr da Silva Brandão Junior; Izabel Cristina Pereira Vaz Ferreira; Emuriela da Rocha Dourado; Cândido Alves da Costa (Semina: Ciências Agrárias, 2013)
Local soil and climate conditions as well as management techniques used in maize cropping affect disease development. In the present study, the incidence and severity of diseases were evaluated in four maize genotypes cultured in three management systems with different technology levels. We tested two landrace varieties from the North of Minas Gerais state, one double-cross hybrid and 1 singlecross hybrid. The experiment was carried out using a randomized block in lays (four varieties and three management systems) and three repetitions. Disease incidence was determined by calculating the percentage of plants with symptoms, and its severity was assessed using a scale diagram to categorize symptom levels from 0 to 5. Results were analyzed using analysis of variance followed by mean contrasts using the Scott-Knott test at a significance level of 0.05. In conclusion, cropping system affects the incidence and severity of southern rust, which is increased by high technology systems. Landrace varieties Argentino and BR da Várzea and double-cross hybrid SHS 4080 have higher resistance to southern rust than single-cross hybrid IAC 8333.